Seasonal physiological responses of Argania spinosa tree from Mediterranean to semi-arid climate - Díaz-Barradas, Mari Cruz; Zunzunegui, María; Ain-Lhout, Fatima; Jáuregui, Juan; Boutaleb, Said; Álvarez-Cansino, Leonor; Esquivias, Mari Paz (Plant and Soil, 2010)
Argania spinosa (the argan tree) is a slowgrowing tree endemic of Morocco, growing on semiarid areas where no other tree species can live. With the aim of predicting temporal changes in A. spinosa woodlands under a probable increase in aridity, we set off to investigate these questions: how do A. spinosa physiological attributes respond to variations in climatic conditions and seasonality, and which is the set of attributes that most affects tree response to environmental conditions? In three study sites, Beni Snassen (North), High-Atlas (Mountain) and Admine Forest in Agadir (Coastal), gas exchange measurements, photochemical efficiency, leaf water potential and different leaf attributes were monitored in February, July and November of 2006. The Mountain site presents the most continental climate. Trees in this site were the most stressed in summer, having the lowest midday leaf water potential values, photochemical efficiency and assimilation rates. We found a Ψmd threshold around -4 MPa, below which stomatal conductance responds linearly to Ψmd . Plants from the North area never reached this threshold during the study period. Although leaf pigments presented a clear seasonal pattern, leaves from Coastal trees exhibit the highest content for each season. The three study sites were separated by two discriminate functions obtained by canonical discriminant analysis. In summer, the Mountain population is separated from the other sites mainly by assimilation rate and Fv /Fm, while in winter transpiration rates and chlorophyll content are the main discriminant variables. Our study shows that A. spinosa trees adjust their physiological status and leaf attributes to environmental conditions allowing plants to thrive under a dry climate. Under a scenario of global change, the distribution of the argan tree likely shifts to milder areas.
Keywords: Browsing; Drought; leaf traits; photochemical efficiency; Stomatal conductance; water relations

Photoinhibition in cork-oak leaves under stress: influence of the bark-stripping on the chlorophyll fluorescence emission inQuercus suber L. - Werner, Christiane; Correia, O. (Trees-Structure and Function, 1996)
Quercus suber is the primary source for industrial cork and becomes bark-stripped every 9 – 10 years. Recurring cork extraction is a major stress factor and the large water loss from the stripped trunk surface may affect the water balance and tree productivity. To evaluate the effect of bark-stripping, fluorescence emission and stomatal conductance of leaves were determined in groups of barkstripped and control trees. Fv/Fm ratio was found to be significantly lower in bark-stripped trees indicating a reduced photosynthetic efficiency of PSII. Photosynthesis was not found to be stomata limited. The reduction in Fv/Fm resulted from a decline in maximum and variable fluorescence while the initial fluorescence of the darkadapted state (Fo) remained constant. A general decline in photosynthetic efficiency of PSII was found in all trees during the summer, probably reflecting the prolonged environmental stresses during a hot and dry season. Additional stress caused by the bark-stripping seems to enhance the susceptibility to photoinhibition of the trees.
Keywords: bark-stripping; fluorescence emission; Quercus Suber L; water relations

Effects of bark-stripping on the water relations of Quercus suber L - Correia, O. A.; Oliveira, G.; Martins-Loução, M. A.; Catarino, F. M. (Scientia gerundensis, 1992)
Quercus suber is the primary source of industrial cork and can produce cork every 9-10 years. The main objective of this work was to investigate the influence of bark stripping on the stomatal activity and water relations of cork-oak. For this purpose, diurnal changes on transpiration, stomatal conductance and water potencial were measured before and after bark stripping during July and August 1989 and 1990. The stripping on the trees had been done at various intensities. The water loss by the stripped surface was also measured. These results show that severe bark-stripping may lead to a decrease in stomatal conductance and considerable water losses. The stripping stress is not clearly dependent on the stripping coefficients, but rather on the water lost by the trunk which varies from tree to tree probably according to the phloemic tissues composition.
Keywords: bark-stripping; Quercus suber; Transpiration; water relations

Use of pressure volume curves in water relation analysis on woody shoots: influence of rehydration and comparison of four European oak species - Dreyer, E.; Bousquet, F.; Ducrey, M. (Ann. For. Sci., 1990)
Pressure volume analyses were undertaken on leafy shoots of 4 European oak species (Quercus robur, Q petraea, Q pubescens and Q ilex) in order to determine the relationship between leaf water potential, average osmotic potential and volume averaged turgor. Some technical limitations of pressure volume analysis, as shown by the influence of the resaturation method on computed turgor, were overcome by accounting for losses of intercellular water during the first stages of dehydration. Variations in leaf to stem ratio, which are very important between large leaved oaks and small leaved evergreens, surprisingly did not influence the relative symplasmic volume of our samples. Differences in mean osmotic potential at full turgor (&Pi0) were related to species, with higher values in drought adapted species, and to leaf age and growing conditions. Values of volumetric modulus of elasticity (ε o) did not significantly influence the relations between leaf water potential (Ψw) and turgor (P) in different species. This relationship was mostly related to &Pi0. Finally, tolerance to drought appeared to be related more to the ability to osmotically adjust in response to changes in environment rather than to the absolute values of &Pi0.
Keywords: pressure-volume curve; Quercus sp; turgor; water potential; water relations